2012
DOI: 10.1002/chem.201103816
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Anisotropy Barriers of Dysprosium(III) Single‐Ion Magnets

Abstract: Magnetic personality: The incorporation of a bulky auxiliary ligand in β‐diketone‐based dysprosium(III) single‐ion magnets (SIMs) remarkably increases the anisotropic barriers, representing a promising route toward the design of higher‐anisotropic‐barrier SIMs (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 223 publications
(103 citation statements)
references
References 33 publications
(18 reference statements)
2
100
1
Order By: Relevance
“…In another study, a small family of structurally similar [Er [112]. Some capping ligands can also cause distortions of the D4d symmetry, which results in larger off-diagonal anisotropy, and implicitly enhanced QTM [113].…”
Section: Peripheral Ligandsmentioning
confidence: 96%
“…In another study, a small family of structurally similar [Er [112]. Some capping ligands can also cause distortions of the D4d symmetry, which results in larger off-diagonal anisotropy, and implicitly enhanced QTM [113].…”
Section: Peripheral Ligandsmentioning
confidence: 96%
“…This provides an initial empirical single-ionic SMM model where the lanthanide ion is located in an antiprism coordination geometry. This model also works well for the single-ionic lanthanide SMMs, which were designed and synthesized early in the development of these compounds, such as the lanthanide polyoxometalates and-diketone-based systems [29][30][31][32][33][34][35] [(Pc 2 )Ln(Pc 2 )] -.TBA + (9b, 10b) can be obtained using the conventional redox reaction [40,41]. A comparative study detected a fairly significant upward temperature shift in the slow relaxation for 9a and 10a compared with that for the corresponding anionic species 9b and 10b with effective barrier heights U eff of 550 and 55 cm -1 for the former two species, respectively.…”
Section: Bis(tetrapyrrole) Lanthanide Smmsmentioning
confidence: 99%
“…In addition, the replacement of auxiliary ligands in some β-diketone-based mononuclear dysprosium compounds has also been shown to play a crucial role in controlling the local coordination geometries of the Dy III ions associated with the relaxation process. 23,27 More importantly, Sessoli and coworkers revealed that even a change in hydrogen bonding in the coordinated water molecule has a significant impact on the orientation of the anisotropy axis in a Dy/DOTA compound (DOTA = tetraazacyclododecane tetraacetic acid). 28 Herein, with the aim of investigating the influence of anion size on the local coordination geometry and eventually the relaxation behavior in Dy III compounds, we employed DyCl 3 , Dy(NO 3 ) 3 , and Dy(ClO 4 ) 3 salts as the origins of anions of different sizes and assembled them with the new aroylhydrazone ligand (3-hydroxy)-N′-((8-hydroxyquinolin-2-yl)-methylene)picolinohydrazide (H 3 L).…”
Section: ■ Introductionmentioning
confidence: 99%